Reklama prasowa – rodzaje i podrodzaje. Sposoby promocji prasy - Mikosz, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
In the text entitled “Press advertising – kinds and subkinds. The ways of the promotion of the press”, the author discusses press advertising, which is a fast developing mass-media phenomenon. Modernity has granted press advertising a high quality of print and paper, as well as infinite possibilities of combining various promotional forms with the press. The present author proves that press advertising is one of the best ways in which a company can communicate with the market. Its advantage is, above all, a high frequency of contents distribution and the possibility of conveying precise and vast advertising information.